Are millennials truly attach and loyal to the human brand ? - Chua, Chee Fong, 1994-, author 612086 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Pengurusan (Pemasaran))